INTEGRASI KURIKULUM INTERNASIONAL DAN NILAI KARAKTER ISLAMI DI MADRASAH: ANALISIS TEORETIS TRANSFORMASI PENDIDIKAN ISLAM MENGHADAPI TANTANGAN GLOBAL - Sururi Ikfi; Mulyono; Luthfia Fathi Pusposari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Islamic education in the era of globalization faces complex challenges characterized by VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) conditions, which necessitate madrasas to transform into competitive institutions without compromising their religious identity. This study aims to analyze the theoretical construction of integrating international curricula and Islamic character values within the framework of transformational leadership in madrasas. Employing a qualitative approach through library research, this study performs a content analysis of relevant primary and secondary literature. The findings indicate that the integration of international curricula, such as the Cambridge standard or the International Class Program (ICP), serves as a fundamental quality differentiation strategy to enhance the global competitiveness of madrasas. Concurrently, the internalization of Islamic character values acts as a cultural and ideological filter, preserving the Muslim identity of students amidst the currents of modernization. The success of this synergistic integration is heavily dependent on transformational leadership, which functions as a cultural architect by providing intellectual stimulation for educators and communicating an integrative vision that unites global academic standards with noble Islamic values. This study concludes that strengthening transformational leadership capacity is a strategic investment for realizing madrasas that are superior, competitive, and consistently religious in the era of disruption